This is service design methods : a companion to this is service design doing - Stickdorn, Marc, ....-; Lawrence, Adam, ....-; Hormess, Markus, ....-; Schneider, Jakob, ....- (Sebastopol : O'Reilly Media Inc., 2018)
In this book, you'll find 54 hands-on descriptions that help you do the key methods used in service design. These methods include instructions, guidelines, and tips-and-tricks for activities within research, ideation, prototyping, and facilitation. This is the print version of the method companion to the book This Is Service Design Doing (#TiSDD). It includes the same content that you can find free on the book website, tisdd.com, but nicely revisualized and presented in a professional bound format. Caveat: While methods are the building blocks of a service design process, owning a pile of bricks does not make you an architect or even a bricklayer. Success in doing service design certainly requires a mastery of these methods. However, you must also be able to combine them into a process that fits the context and needs of your organization and guide people through this new way of working. This book only contains the building blocks-the methods. It doesn't detail how to assemble them into a cohesive design process or how to plan or manage it. Neither does it describe why people should invest in service design nor explain how to bring service design to life in your organization. For all of this (and more), please read This Is Service Design Doing.
Keywords: Industrieel ontwerpen; Productontwerpen